A method for sequencing single-stranded cloned DNA in both directions. Issue 3 (March 1981) - Hong, G. F.
Abstract : A DNA sequencing method has been developed whereby DNA that has been cloned in a single-stranded bacteriophage vector can be sequenced from both ends. The method involves first making a minus-strand sense template from a single-stranded insert in the vector MJ3mp2 using a flanking primer, and then sequencing the synthesized template using the dideoxynucleotide termination method (Sanger et al., 1977, 1980) with a second primer. Special conditions are described under which the first primer is easily removed after making the templat% and sequencing in the opposite direction can be done in the normal way (Sanger et al., 1980) without separating the double strands. This method renders it possible to read up to twice the amount of sequence data from a long insert and also to check short inserts by producing complementary sequence patterns.